Genes underlying adaptive response to solar radiation in plants - (:unkn) unknown (My University, 2025)
The aim of this project is to characterize genes underlying reproductive isolation and adaptation of plants to environmental heterogeneity
Keywords: Ecological genomics; high throughput sequencing